Injuries and Complications Management with Forsus Appliance - Ghislanzoni, Luis Huanca; Lucchese, Alessandra; Tagliatesta, Costanza (Orthodontic Journal of Nepal, 2017)
Introduction: Forsus is a useful appliance for non-compliant Class II problems, however various problems can occur when using them. Objective: To demonstrate a comprehensive series of of critical situations that can occur using the Forsus device and to provide the possible solutions of each complication. Materials & Method: The clinical management of the Forsus appliance was analyzed for eighty consecutively treated patients. The Forsus was used five months on average and pictures and clinical record were registered each time a patient had a problem or an injury. Discussion: The most common problem was breakage of the appliance. Breakage could occur as debonding of the lower first premolars or unsoldering of the upper first molar tubes. Lower premolar debonding could be prevented and fixed with an extra layer of flow composite surrounding the bracket base. Lesions of the cheek mucosa were found in several patients. A soft cotton pad used as “wax” was an effective solution to allow soft tissue healing and to prevent spring rubbing against the cheek. Upper molar intrusion occurred mainly when second molars were not included in the upper arch. Some patients experienced disconnection of the spring and the push rod while opening the mouth wide. They were taught to self-adjust the appliance. Conclusion: The use of the Forsus appliance may lead to relatively frequent problems that the orthodontist can easily prevent and manage.